Polish Adaptation of the Basic Psychological Need Satisfaction and Frustration Scale - Kuźma, Beata; Szulawski, Michał; Vansteenkiste, Maarten; Cantarero, Katarzyna (Frontiers in Psychology, 2020)
This article presents the findings of four studies designed to validate the translated Polish version of the Basic Psychological Need Satisfaction and Frustration Scale (Chen et al., 2015). Results of exploratory factor analyses in Study 1 (N = 272, Mage = 41.07) showed that the psychological need for autonomy, relatedness, and competence that are central to Self-Determination Theory (Ryan & Deci, 2017) have a bi-dimensional structure, involving both a need satisfaction and need frustration component. Subsequent confirmatory factor analyses in Study 2 (N = 265; Mage = 38.15) provided further evidence for a six-dimensional structure of the scale, thereby distinguishing a satisfaction and frustration component for each of the three needs. Study 3 (N = 158; Mage = 27.28) further revealed that the distinguished subscales are moderately to highly internally consistent and yielded good test-retest reliability. Finally, Study 4 (N = 204; Mage = 20.57) confirmed that satisfaction of the needs is positively related to well-being, while frustration is positively related to depressive symptoms. The Polish version of the BPNSF Scale can be successfully used in future basic and applied studies in the context of Self-Determination Theory.